2017
DOI: 10.1017/neu.2017.24
|View full text |Cite
|
Sign up to set email alerts
|

Auditory brainstem response (ABR) profiling tests as diagnostic support for schizophrenia and adult attention-deficit hyperactivity disorder (ADHD)

Abstract: The ABR profiling tests discriminated schizophrenia and ADHD versus healthy controls with high sensitivity and specificity. The methods deserve to be further explored in larger clinical studies including a broad range of psychiatric disorders to determine their utility as potential diagnostic biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
(46 reference statements)
1
8
1
1
Order By: Relevance
“…The major finding of the present study is that the ABR profiling test of SZ was positive for only 31% and negative for 69% in the group of patients with SZA. In contrast, the results from the previous study by Juselius Baghdassarian et al (2018) showed that 22/ 26 (85%) of patients with clinical SZ were positive and 4/26 (15%) negative for SZ using ABR profiling. In a group of 58 healthy controls, 4 (7%) were false positives and 54 (93%) were true negatives for SZ, and in a group of 24 patients with ADHD, 2 (8%) were false positives and 22 (92 %) were true negatives for SZ.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The major finding of the present study is that the ABR profiling test of SZ was positive for only 31% and negative for 69% in the group of patients with SZA. In contrast, the results from the previous study by Juselius Baghdassarian et al (2018) showed that 22/ 26 (85%) of patients with clinical SZ were positive and 4/26 (15%) negative for SZ using ABR profiling. In a group of 58 healthy controls, 4 (7%) were false positives and 54 (93%) were true negatives for SZ, and in a group of 24 patients with ADHD, 2 (8%) were false positives and 22 (92 %) were true negatives for SZ.…”
Section: Discussioncontrasting
confidence: 57%
“…Utilising new techniques of analysing digitised auditory brainstem response (ABR) waveforms, gender-specific ABR profiling has permitted identification of patients with schizophrenia (SZ) versus healthy controls and versus adult attention-deficit hyperactivity disorder (ADHD) patients with high sensitivity and specificity (Källstrand et al, 2016). A separate study with blind evaluation of the ABR profiling methods obtained similar results (Juselius Baghdassarian et al, 2018). Thus, the ABR profiling test for SZ differentiated patients with SZ versus healthy controls with an accuracy of 90.5% receiver operating characteristic curve (ROC area 0.92) and versus patients with ADHD with an accuracy of 88.0% (ROC area 0.94).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…ABR measurements are well-known in clinical neurological practice and may be relevant to further investigate the potential early involvement of the lower brainstem in PD pathology (75). Nonetheless, bilateral central ABR prolongations have been reported in a wide variety of neurological conditions (e.g., demyelinating diseases, Alzheimer's disease, schizophrenia) (74,149,150) which may affect the specificity of ABR measurements as a marker of prodromal PD. Regarding intensity dependence paradigms, an increased IDAEP of the N1/P2 component has been found in early stage patients with PD compared to HCs suggesting lower serotonergic activity and related depression in PD (108,151).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sköld et al demonstrated higher ABR-waves III and VII plus thalamo-cortical aberrances related to affective disorder [7]. In view of results from other psychiatric disorders on the brain stem [Schizophrenia, ADHD (Attention Deficit Hyperactivity Disorder) and ASD (Autism Spectrum Disorder)] it would be supposed that depression might show ABR aberrances as well [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%